1968
DOI: 10.3758/bf03342412
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting children’s alternation and choice behaviors

Abstract: Following 0, 3. fl. 12, or 24 exposures to a red or a green light, 6-, 7-, and 8-year-old childnm were required UII each of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0

Year Published

1969
1969
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…The results are also consistent with Croll's( 1966) failure to find a significant within-Ss effect of StD. Manley & Miller (1968) found response duration to significantly affect alternation behavior. Thus, it appears that lwahara & Sugimura (1959) found a significant effect of StD on SA only because StD was confounded with response duration.…”
supporting
confidence: 80%
“…The results are also consistent with Croll's( 1966) failure to find a significant within-Ss effect of StD. Manley & Miller (1968) found response duration to significantly affect alternation behavior. Thus, it appears that lwahara & Sugimura (1959) found a significant effect of StD on SA only because StD was confounded with response duration.…”
supporting
confidence: 80%
“…Thus, time is relatively uninformative in studies of children's alternation behavior in a cross-maze. DISCU8SION The increased rate of alternation obtained with Ss who started from the same start position on each of two trials is in agreement with the results from studies with human Ss performing other tasks (Manley & Miller, 1968;Miller, Tu, Moffat, & Manley, 1969) and from studies with animals (Goodrick, 1967;Hughes, 1968a, b;Kirkby & Lackey, 1968;Williams, Carr, & Peterson, 1966). It appears that the rate of alternation increases linearly over ages 3 to 6, as shown in the present study.…”
Section: Subjectssupporting
confidence: 78%
“…It appears that the rate of alternation increases linearly over ages 3 to 6, as shown in the present study. However, the increase does not continue linearly, since Miller et al (1969) found that 7-year-old children alternated at a higher rate than 10-year-olds, and Manley & Miller (1968) found that 7-year-old Ss alternated at a higher rate than 8-year-old Ss. Thus, it seems that, under constant conditions, the alternation rate increases until the child is 7 years old and then perhaps declines or remains stable.…”
Section: Subjectsmentioning
confidence: 96%
“…A more accurate observation (Weir, 1967) is that the alternation response pattern does not drop out compietely untiI about Age 12. Also of interest is a comparison of these results with those of Manley & Miller (1968). 80th studies indicate that 7-year-olds alternate more frequently than other Ss in the 4-to IO-year-old age group.…”
mentioning
confidence: 88%
“…Second, STD and response duration (RD) appear to have been confounded in the Iwahara & Sugimura (1959) study. Subsequent research (Manley & Miller, 1968) indicates that RD is a variable which affects alternation behavior. Despite these reservations, the Iwahara & Sugimura (1959) study does suggest that STDs longer than those employed by CroU (1966) and Rabinowitz (1965) may produce effects on children's alternation behavior.…”
mentioning
confidence: 99%